Risk Factors for Acute Kidney Injury in COVID-19 Patients: A Systematic Review - Daniella, Dian; Kandarini, Yenny; Mahadita, Gede Wira (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Acute kidney injury (AKI) in coronavirus disease-19 (COVID-19) has high incidence and mortality. Risk factors for AKI in COVID-19 patients are not well explored. This systematic review provides a combination of available evidence regarding risk factors of AKI in COVID-19 patients. METHODS: A systematic research was performed in Medline, Cochrane Central Register of Controlled Trials, and ScienceDirect journal databases from 2019 to August 2020. The study selection process was plotted using a Preferred Reporting Items for Systematic Review and Meta-Analyses flow diagram. RESULTS: Out of 553 studies found, four full-text studies met the inclusion criteria and were included in qualitative analysis. There are 2205 COVID-19 patients with AKI (36.44%) from 6051 COVID-19 patients. Age was a risk factors for AKI in two studies (odds ratio [OR] 1.03 [p < 0.001], OR 1.03 [p < 0.007]). Critical condition of patient is risk factors for AKI (OR 8.155 [p = 0.006]). Hirsch et al. stated that diabetes mellitus (OR 1.74 [p < 0.001]), cardiovascular disease (OR 1.48 [p < 0.001]), and hypertension (OR 1.25 [p = 0.02]) are also risk factors. Laboratory results such as elevated procalcitonin (PCT) and estimated glomerular filtration rate (eGFR) <60 ml/min/1.73 m2 showed positive association to AKI in COVID-19 patients (OR 4.822 [p = 0.037]; OR 13.451 [p = 0.016]). A higher sequential organ failure assessment (SOFA) score at admission is one of the risk factors (OR 1.498 [p = 0.027]). CONCLUSION: Demographics, clinical classification of COVID-19, comorbidities, SOFA score, PCT, and eGFR can help clinicians predict AKI in COVID-19 patients.